PROFIL KEMAMPUAN KONEKSI MATEMATIS SISWA DALAM MENYELESAIKAN MASALAH OPIMALISASI DITINJAU DARI KEMAMPUAN MATEMATIKA: Profile Of Students' Mathematical Connection Ability In Solving Optimization Problems As Seen In The Face Of Mathematical Ability - Zulkifli; Karniman, Tegoeh S.; Hasbi, Muh. (Universitas Tadulako, 2024)
This study aims to obtain a description of the mathematical connection ability of students of class XI IPA SMA Negeri 2 Kasimbar on optimization material. This type of research is descriptive with a qualitative approach. The subjects of this study were students of class XI IPA SMA Negeri 2 Kasimbar with high, medium and low math abilities. Date were collected through written tests and interviews. The results of this study indicate that subjects with high mathematical abilities HD can use the relationship between mathematical concepts on the problem to be solved, can use the relationship between concepts and procedures and arithmetic operations in solving problems outside of mathematics and can apply mathematical concepts to other fields of study. Subjects with medium mathematical abilities MU can use the relationship between mathematical concepts on the problem to be solved, can use the relationship between concepts and procedures and arithmetic operations in solving problems outside of mathematics and can apply mathematical concepts to other fields of study. Subject with low math abilities RY can apply mathematical concepts to other fields of study.